To the Threshold of Power, 1922/33 Origins and Dynamics of the Fascist and Nationalist Socialist Dictatorships :Volume 1 - Knox, MacGregor (Cambridge University Press, 2013)
This is an unfashionable book. The 1960s taught me the necessity of defying the wisdom of the tribe, even the tribe of the intellectuals. The book breaks a number of conventions, most of which I spell out in the introduction. But its mortal sin is to take seriously Thucydides’ insistence that human history is the history of power – dynamis – and of armed conflict. Much of this first volume may not seem explicitly concerned with warfare, the central feature and supreme purpose of the regimes whose advent, nature, and workings it seeks to explain. But war is ever-present, even in my imprudent excursions into economics, social and political structures, and the realm of ideas. Clausewitz memorably insisted that “the soldier is recruited, clothed, armed, and drilled, [and] sleeps, eats, drinks, and marches, only for this: that he should fight in the right place at the right time.” This volume establishes the logistical base and conducts the long approach march toward an understanding of the supremely violent careers of the Fascist and Nazi regimes. Its successor will build on that foundation in analyzing the outcomes, from the respective “seizures of power” in 1922–26 and 1933–34 to common ruin in 1943–45